Short-term progression of interstitial lung disease in systemic sclerosis predicts long-term survival in two independent clinical trial cohorts. Issue 1 (8th November 2018) - Volkmann, Elizabeth R; Tashkin, Donald P; Sim, Myung; Li, Ning; Goldmuntz, Ellen; Keyes-Elstein, Lynette; Pinckney, Ashley; Furst, Daniel E; Clements, Philip J; Khanna, Dinesh; Steen, Virginia; Schraufnagel, Dean E; et al.
Abstract : Objective: To assess survival and identify predictors of survival in patients with systemic sclerosis-interstitial lung disease (SSc-ILD) who participated in the Scleroderma Lung Studies (SLS) I and II. Methods: SLS I randomised 158 patients with SSc-ILD to 1  year of oral cyclophosphamide (CYC) vs placebo. SLS II randomised 142 patients to 1 year of oral CYC followed by 1 year of placebo vs 2 years of mycophenolate mofetil. Counting process Cox proportional hazard modelling identified variables associated with long-term mortality in SLS I and II. Internal validation was performed using joint modelling. Results: After a median follow-up of 8 years, 42% of SLS I patients died, and when known the cause of death was most often attributable to SSc. There was no significant difference in the time to death between treatment arms in SLS I or II. Higher baseline skin score, older age, and a decline in the forced vital capacity (FVC) and the diffusing capacity for carbon monoxide (DLCO) over 2 years were independently associated with an increased risk of mortality in SLS I. The Cox model identified the same mortality predictor variables using the SLS II data. Conclusion: In addition to identifying traditional mortality risk factors in SSc (skin score, age), this study demonstrated that a decline in FVC and DLCO over 2 years was a better predictor of mortality than baseline FVC and DLCO. These findings suggest that short-term changes in surrogate measures of SSc-ILD progression may have important effects on long-term outcomes.